"A Salisbury steak is not a steak, it's ground beef." The significance, messages and symbolism of final meals on death row. (1st January 2020) - van Hagen, Eline
Abstract: The last meal on death row is a person's very last opportunity to eat. It marks the upcoming execution of that person. Therefore these meals represent meaning, symbolism and paradoxes, especially since inmates are free to choose what their last supper will consist of. By connecting investigated last meals in the 20th century from different states in the USA with several theoretical ideas, an attempt is made to shed light on the significance of this meal. Concepts like commensality, agency, power relations and the cultural importance and symbolism of the Christian last supper are viewed upon in the context of prison life. In doing so, the contradictions and paradoxes that characterize the phenomenon of this meal are analyzed. The messages that last meals can carry can be explicitly strong and often function as inspiration for artists as well as human rights activists. Many art projects are based on the concept of the last meal – often with the purpose to criticize the death penalty. Apart from the cultural significance of the last meal, the psychological impact of food in confined situations is also investigated, as well as the practical opposite of the special meal request on death row: the specific wishes for a first meal to eat once released from prison.